Meta-análise: transtorno do espectro autista e memória operacional - Ferraresi, Tatiane Santana Prado (2021)
Scientific literature indicates losses in the performance of working memory (WM) in people who are within the framework of the Autism Spectrum Disorder (ASD), but there are divergences among which WM subsystems would be affected. In this work we selected peer-reviewed experimental research articles which had compared the performance of ASD participants to those of participants with typical development, aged between 5 and 18 years old. Only studies published in the English language, in which the participants of the ASD groups were diagnosed according to one of the following tools, were included: the International Classification of Diseases (ICD) 9th, 10th and 11th; the Diagnostic and Statistical Manual of Mental Disorders III, IV and V; the Autism Diagnostic Observation Schedule, and/or; the Autism Diagnostic Interview-Revised. Papers also had to contain enough information to calculate the effect size of each study, and to present behavioral data and the assessment of an intelligence quotient (IQ), using it as a selection criteria for the participants (IQ ≥ 70). The results show the existence of a significant impairment in the performance of the ASD group in comparison to the control group, especially in tasks and tests aimed to evaluate the visual-spatial WM, but we also verified impairment in the performance of verbal WM to a lesser extent. These findings broaden, and confirm, the results of previous works (Habib et al., 2019; Lai et al. 2017; Kercood et al. 2014; Wang et al. 2017). The results contribute to identify cognitive functions that are possibly impaired in ASD subjects, and to guide interventions that can improve their quality of life.